2015
DOI: 10.4028/www.scientific.net/amm.799-800.434
|View full text |Cite
|
Sign up to set email alerts
|

Study the Role of Friction Stir Welding Tilt Angle on Microstructure and Hardness

Abstract: This paper presents an investigation of research objectives on the effect of tilt angle on microstructure and mechanical properties of dissimilar aluminum alloy sheets between AA5083 and AA6061, 5mm plates by using Friction Stir Welding (FSW) process in butt joint. The base materials of AA5083 and AA6061 were located on the retreating side (RS) and advancing side (AS), respectively. The welding process and the welding parameters such as tool pin profile, tool rotation speed, welding speed and tilt angle influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Furthermore, the effect of tilt angle on microstructure and mechanical properties of dissimilar AA5083 and AA6061 FSWed joints demonstrated that the tilt angle of 3 • led to the optimal hardness and microstructure results. The lower tilt angle (0-2 • ) resulted in a tunnel defect, and the higher tilt angle (4 • ) caused grain growth and dissolution of strengthening precipitates in AA6061 [159]. Furthermore, Dialami et al [50] observed that the tool tilt angle increased the temperature in the weld area and facilitated the material flow [50].…”
Section: Effect Of Tool Tilt Angle and Plunge Depthmentioning
confidence: 99%
“…Furthermore, the effect of tilt angle on microstructure and mechanical properties of dissimilar AA5083 and AA6061 FSWed joints demonstrated that the tilt angle of 3 • led to the optimal hardness and microstructure results. The lower tilt angle (0-2 • ) resulted in a tunnel defect, and the higher tilt angle (4 • ) caused grain growth and dissolution of strengthening precipitates in AA6061 [159]. Furthermore, Dialami et al [50] observed that the tool tilt angle increased the temperature in the weld area and facilitated the material flow [50].…”
Section: Effect Of Tool Tilt Angle and Plunge Depthmentioning
confidence: 99%
“…They obtained 1degree as the best tilt angle for a defect-free welding with high mechanical properties. Hamid and Roslee [14] investigate the tilt angle effect on microstructural and mechanical characteristics of FSWelded dissimilar aluminum alloys. They observe that the tilt angle affects the mechanical properties of the FSW joints considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Results revealed that tensile strength is increased at higher rotational speeds and lower welding speeds. Hamid and Roslee [3] concluded that increased tilt angle produces reduction in strength of the weld during FSW of AA5083 and AA6061. Masoud Ahmadnia et al [4] optimized welding parameters while FSW of AA6061 and AA5010.…”
Section: Introductionmentioning
confidence: 99%